Rancang Bangun Rangka Sepeda Listrik Roda 3 untuk Mobilitas Laboratorium Berkapasitas 150 KG - Fadly Achmad Azhar; Zainuddin; Leo Van Gunawan (Journal of Applied Mechanical Technology, 2025)
ABSTRACT – The ease of moving from one place to another, especially to carry equipment or test results, is an important necessity. However, accessibility and mobility efficiency are often an obstacle, even more so for individuals with physical limitations. Tricycles provide better stability compared to two-wheeled bicycles, making them suitable for operations in campus or laboratory environments that have limited terrain and are densely active. This research aims to design and construct a three-wheeled electric bicycle frame to support laboratory mobility with a maximum load capacity of 150 kg. The design process follows the Pahl and Beitz method for concept development, with three-dimensional modeling conducted using SolidWorks software, and structural strength analysis performed through Finite Element Analysis (FEA). Manual calculations were also carried out to validate the numerical simulation results. The manufacturing stage involved cutting, bending, and welding hollow steel pipes, with considerations for ergonomics and cost efficiency. Simulation testing indicated a maximum stress of 30.3 MPa, which is significantly lower than the yield strength of ASTM A36 material, resulting in a high safety factor of 8.2. This research contributes to the development of environmentally friendly, efficient, and safe transportation solutions for research environments.